Pengaruh Eco-Enzyme dari Kulit Jeruk dalam Menghambat Pertumbuhan Bakteri E.coli - Maharani, Dinda (Poltekkes Kemenkes Denpasar, 2025)
ABSTRACT Efforts to prevent the entry of pathogenic E. coli that cause infections can be done by suppressing the growth of these bacteria. The material used to inhibit the growth of these bacteria uses orange peel eco-enzyme which is antibacterial and indirectly reduces organic waste. This study aims to determine the effect of orange peel eco-enzyme in inhibiting the growth of E. coli bacteria in NA media. The quasi-experimental study used orange peel eco-enzyme liquid. The eco-enzyme concentration used was 25%, 50%, 75% and 100%. The parameter measured was the diameter of the inhibition zone formed. The results of the study obtained by the t-test of the effect of orange peel eco-enzyme at concentrations of 25%, 50%, and 75% showed no difference in inhibitory power, except at a concentration of 100% where (p value = 0.05). From the one-way ANOVA test, it was known that the difference in the inhibitory power of E. coli bacteria compared to the concentration tested, the results obtained were significant differences. The inhibitory power of E. coli bacteria was classified as low.